Where next? The emergence of hypervirulent W meningococcus in the Netherlands - Snape, M; Broad, J (Elsevier, 2017)
In The Lancet Public Health, Mirjam Knol and colleagues provide useful data on the recent emergence and spread of the so called original UK strain and the 2013 strain of the hypervirulent sequence type 11 clonal complex (cc11) of meningococcal serogroup W disease in the Netherlands and England. As a result of these descendants of the South American 2003 strain, capsular group W now accounts for 30% of all meningococcal disease in England, while the 2013 strain is primarily responsible for the current outbreak in the Netherlands. The similarities between the outbreaks in England and the Netherlands are striking; in both countries an increase was first seen in adults aged older than 65 years, both had a substantial proportion of patients with atypical presentations (including pneumonia, gastrointestinal symptoms, and septic arthritis), and fatality rates were relatively high in both settings (11% in the Netherlands and 12% in England). As well as being important in their own right, these data raise the possibility that this hyperinvasive strain could continue to spread, and indeed the authors mention preliminary reports of increases in serogroup W disease in Germany, France, Spain, and Sweden. Meanwhile, a similar increase in serogroup W disease due to a hypervirulent cc11 strain (the ancestor of the UK strains) has been reported in Latin America and Australia.